From anthropocentrism to ecocentrism: The role of local wisdom and religious tradition in transforming environmental ethics - Haniifa, Rahmadita; Palimirmo, Rian (Holistic: Journal of Tropical Agriculture Sciences, 2025)
Background: Bali is one of the islands in Indonesian archipelago that has the most beautiful tourist destinations and always gets visits from local and non-local tourists. The growth of Bali’s tourist destinations makes Bali must expand tourist areas such as hotels, restaurants, and areas that can increase the visits of local and non-local residents. As a result, Bali has occurred massive cover change to land use and some vegetation degradation that causes environmental damage. There is still an ethic of anthropocentrism in managing Bali’s environment. The ethics of ecocentrism have been applied in most Balinese communities but most also still adhere to the ethics of anthropocentrism, the need for ecocentrism ethics to be developed throughout of the community to manage the natural environment properly. Methods: This research uses a qualitative method, conducted by analyzing the problems that exist in Bali. Data collection uses literature study-based method that is related to environmental management from the point of view of ecocentrism in Bali. The analysis is carried out by providing description related to the perception of Balinese people in environmental management and culture values that can be used as guidelines in environmental management. Findings: Balinese people, especially Hindus, have practiced ecocentrism paradigm quite well towards the environment. Balinese Hindus apply Tri Hita Karana in managing and conserving the natural environment, especially water and forests. Preservation of the natural environment is one of the important things in Hinduism because it is one of their ritual parts. Conclusion: In managing the natural environment, especially water and forests, it cannot be separated from the local wisdom of Balinese Hindus culture, including tumpek wariga, tumpek uye and wana kertih. Therefore, it can be concluded that Balinese people have implemented ecocentrism ethics. Novelty/Originality of this Article: This study provides a cultural perspective on environmental ethics by emphasizing the integration of Balinese Hindu local wisdom, such as Tri Hita Karana, tumpek wariga, tumpek uye, and wana kertih, in practicing ecocentrism for sustainable environmental management.